2022
DOI: 10.1039/d2sc03205h
|View full text |Cite
|
Sign up to set email alerts
|

Short peptide-based cross-β amyloids exploit dual residues for phosphoesterase like activity

Abstract: Herein, we report that short peptides are capable of exploiting their anti-parallel registry to access cross-β stacks to expose more than one catalytic residue, exhibiting the traits of advanced binding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Among the above-mentioned enzymatic activities, the esterase activity of the proteins is well studied, which proceeds through the rapid cleavage of the ester bond. It is important to mention that the cleavage of an ester bond is triggered by various amino acid residues of the protein, such as tyrosine, histidine, arginine, lysine, etc., through a concerted protonation–deprotonation pathway. , Transferrin also has these amino acid residues throughout the polypeptide backbone, but the amino acids residing in close proximity to the Fe center (please refer to Figure ) are the focus of this present investigation. Such specific structural features of this metalloprotein motivated us to investigate its esterase-like activity, which can be strategically modulated by altering the conformations of protein using various external agents.…”
Section: Resultsmentioning
confidence: 99%
“…Among the above-mentioned enzymatic activities, the esterase activity of the proteins is well studied, which proceeds through the rapid cleavage of the ester bond. It is important to mention that the cleavage of an ester bond is triggered by various amino acid residues of the protein, such as tyrosine, histidine, arginine, lysine, etc., through a concerted protonation–deprotonation pathway. , Transferrin also has these amino acid residues throughout the polypeptide backbone, but the amino acids residing in close proximity to the Fe center (please refer to Figure ) are the focus of this present investigation. Such specific structural features of this metalloprotein motivated us to investigate its esterase-like activity, which can be strategically modulated by altering the conformations of protein using various external agents.…”
Section: Resultsmentioning
confidence: 99%
“…Another peptide derivative of KLVFFAL that replaced lysine and leucine with arginine and histidine respectively (peptide RLVFFAH) self-assembled into amyloid-like nanotubes that catalyzed the hydrolysis of different phosphoester bonds that partially mimic the activity of canonical enzymes such as RNase, DNase, and phosphatase [ 72 ]. The assemblies exhibited cofactor-independent hydrolytic activity towards the RNA-like compound hydroxypropyl-4-nitrophenylphosphate, the DNA-like substrate Bis (4-nitrophenyl)phosphate, and pNPO as a substrate surrogate of phosphatase.…”
Section: Peroxidase-like Activitymentioning
confidence: 99%
“…10 Synthesized peptides containing core sequences of natural amyloid proteins have been reported to spontaneously assemble into amyloid-like brils in vitro. 4,[11][12][13] In particular, the core sequence of Ab (Ab: [16][17][18][19][20][21] KLVFFA) can self-assemble into amyloid-like brils with antiparallel b-sheet structures. [14][15][16] Recently, Das et al developed catalytic amyloids by introducing functional groups into the edges of the core peptide.…”
mentioning
confidence: 99%
“…[14][15][16] Recently, Das et al developed catalytic amyloids by introducing functional groups into the edges of the core peptide. [17][18][19] Additionally, based on de novo synthetic peptides, catalytic amyloids containing metal ions as cofactors have been used to mimic enzymes in several hydrolysis and oxidation reactions. Korendovych et al showed that an amyloid-forming de novo peptide (Ac-IHIHIQI-NH 2 ) can coordinate with metal ions, such as Co 2+ , Cu 2+ , or Zn 2 , aer which the Zn 2+ -loaded amyloid brils catalyse acyl ester hydrolysis 20 whereas the Cu 2+ -loaded structures activate oxygen molecules to catalyse the oxidation of dimethoxyphenol.…”
mentioning
confidence: 99%